ENHANCING STUDENTS’ ENGLISH GRAMMAR ABILITY WITH ONLINE WEBSITE LINK - Nur Ekaningsih (EduLite: Journal of English Education, Literature and Culture, 2017)
Today’s activities are now using technology not only on business activities but also education. There are so many facilities on technology especially for improving students’ capability in learning knowledge such as e-learning and distance learning course. Lecturers as the facilitator in transferring knowledge, it is very beneficial to master good technology when they deliver knowledge. As written by Dick et al. (2005) that students are carried together with lecturer or on-line content, and are guided through class actions such as on-line exercises, discussion board and interaction with classmates. This occurred also for English lecturers to do teaching learning process. In this classroom action research which is done at English Education Department of UNISSULA on the third semester, the researcher shows new interesting classroom website on-line activities in learning English grammar. Using useful on-line link sources of students’ classroom for two cycles makes the students’ grammar capabilities improved better. The result of average class scores improved suggestively from 83 on the first cycle then 88 on the second cycle. So, suitable access to students on searching learning materials from internet must be provided well with preparation before action.